Diagenesis of tight oil sand reservoirs: Upper Triassic tight sandstones of Yanchang Formation in Ordos Basin, China. (26th April 2017) - Dou, Wenchao; Liu, Luofu; Wu, Kangjun; Xu, Zhengjian; Feng, Xu
Abstract : Upper Triassic sandstones in the Ordos Basin, northern‐central China, comprise tight oil reservoirs. Using a combination of thin sections, SEM, BSE, EDS, XRD, and fluid inclusion analyses, 24 core samples from 13 wells were collected to study the petrology, paragenesis, and diagenetic processes and implications for reservoir quality. Quartz cement usually occurs as overgrowths or euhedral quartz. Extensive dissolution and albitization of K‐feldspar can be observed. Five types of carbonate cements, ferrocalcite, ankerite, dolomite, calcite, and siderite, occur during different diagenetic stages. Two main types of illite and 5 main habits of chlorite are observed in this study. Kaolinite mainly occurs as booklets and vermicular aggregates. Diagenetic illite, chlorite, biotite, mixed‐layer illite/smectite (I/S), and other minor minerals are also observed. The diagenetic processes include compaction, alteration of volcanic materials and mica, clay mineral transformation, cementation (silica, aluminosilicate, and carbonate), and dissolution of feldspars and rock fragments. Compaction was a significant porosity‐reducing agent, and the presence of carbonate cement exerts a dominant impact on the reduction of porosity. Quartz cement and authigenic clays are less important; however, it is worth mentioning that pore‐lining clays are conducive to porosity preservation. In this study, most of the porosity variation is caused by a combination of compaction, carbonate cements, quartz cement, and authigenic clays. This study gives insights into diagenetic alterations within tight sandstones and has implications for reservoir quality prediction in similar settings.